Alcoholysis approach for an efficient and cleaner production of diosgenin by low cost and green carbon based solid acids from biomass residues. (10th January 2022) - Jiang, Wenxiu; Yu, Xuejun; Yuan, Hui; Zhang, Ming; Shen, Bowei; Pan, Zhiquan; Zhou, Hong
Abstract: Aiming to achieve more efficient and cleaner production of diosgenin, the waste liquid and residue in the process should be minimized or utilized. An alcoholysis approach was adopted to obtain diosgenin from zingiberensis C. H. Wright (DZW) using carbon-based solid acids as catalysts, which were prepared from the residues of the process via in situ carbonization and sulfonation. Solid acids were also subjected to a full range of physicochemical characterizations. The single factor and response surface methods were used to optimize the production process parameters of diosgenin. The best yield of hydrolysis with glycolic acid is 22.40%, which is 18.55% higher than traditional hydrolysis with sulfuric acid. The solid acids can be reused for 5 cycles with less loss of activity. Importantly, after a simple regeneration procedure, it can be further recycled another 5 times and maintain the same activity as before. Possible alcoholysis routes and mechanisms were analyzed by liquid chromatograph-mass spectrometer, which has an important application foreground in diosgenin production. Graphical abstract: Image 1